Hepatorenal Protective Effects of Hydroalcoholic Extract of Solidago canadensis L. against Paracetamol-Induced Toxicity in Mice - Omid Rahimi; Nilufar Asadi Louie; Alireza Salehi; Firouz Faed Maleki (Journal of Toxicology)
Paracetamol (AKA acetaminophen) is a widely used drug and is used for mild to moderate pains, such as mild osteoarthritis, toothache, headache, and pain caused by minimally invasive surgeries. Despite being a harmless drug in lower doses, acetaminophen can be toxic to the liver and kidneys if overdosed and even results in death. In this study, the therapeutic effects of Solidago canadensis L. extract (SCE) were investigated. 48 adult male Swiss albino mice (20–30 grams) were randomly divided into six groups of 8. The control group was gavaged with normal saline every 12 hours for 6 days. The second group received paracetamol at a 500 mg/kg intraperitoneally (i.p) dose on the sixth day. The third, fourth, and fifth groups were gavaged doses of 125, 250, and 500 mg/kg of SCE every 12 hours for six days, respectively, and on the sixth day, we received paracetamol at a dose of 500 mg/kg i.p. The sixth group only received SCE every 12 hours at a dose of 1000 mg/kg via gavaging for six days. On the seventh day (24 hours after paracetamol injection), blood samples were collected to measure the serum level of creatinine, uric acid, blood urea nitrogen (BUN), total protein, albumin, alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), and total and direct bilirubin, and liver and kidney tissues were also sampled for histopathological examination. It was observed that paracetamol caused a considerable increase in the ALT, AST, ALP, uric Acid, and BUN levels (P<0.01), while those in SCE-treated groups were significantly lower. In addition, various lesions in the paracetamol group were observed, while in the SCE-receiving groups, receiving prophylactic SCE inhibited the high-intense lesions such as the infiltration of inflammatory cells, hyperemia, and vacuolar degeneration, which decreased significantly in the control group in comparison with that of the paracetamol group (P<0.05). In conclusion, SCE can have substantial protective effects against paracetamol’s hepatorenal toxicity.